Persepsi Followers dalam Postingan Akun Instagram Bengkulu Info : Studi Kasus Mahasiswa Jurnalistik Universitas Bengkulu - Gultom, Fransiska Filisia (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
Communication is a process of conveying messages containing information by one person to another person, the aim of which is to inform and make changes, both changes in attitudes and behavior, which can be done directly or indirectly, as well as through any media. Social media has become an increasingly popular platform for obtaining information. The Instagram account @bengkuluinfo is a well-known Instagram account in Bengkulu for providing information and currently has 470 thousand followers, which were formed since February 28, 2018. Through this case study, research will be carried out to explore the extent of followers, especially journalism students in the class of 2020 at Bengkulu University. appreciate, trust, and consider the content presented by the Bengkulu Info Instagram account to be relevant. The method used in this research is the qualitative method. The population to be used is the Bengkulu University class of 2020 journalism students. The sample consists of 3 informants who were selected using purposive sampling. The research results show that the majority show appreciation for the usefulness of the information shared; the critical response from a small portion of the audience is also an important consideration for improving and increasing the quality of the journalism they offer.